Influência do histórico familiar de diabetes mellitus e do exercício físico na glicemia e modulação autonômica cardíaca após ingestão de dextrose - Lozada Tobar, Karen Dennise (2024)
Anomalies in glycemic control were observed in individuals with a family history of diabetes. However, it is still unclear whether these changes in offspring of diabetic parents (FHD+) result in an exacerbated glucose response after carbohydrate consumption. This hyperglycemia may expose the body to an imbalance in glycemic control, increasing the risk of diabetes and impacting cardiac autonomic modulation. Due to its acute benefits, aerobic exercise has been shown to be effective in preventing type 2 diabetes mellitus (T2DM). Previous studies have demonstrated the beneficial effects of aerobic exercise on glycemic control before a carbohydrate overload in various populations, but these effects have not yet been investigated in FHD+ and their relationship with heart rate variability (HRV). Therefore, the aim of this study is to evaluate whether a family history of type 2 diabetes influences glycemia and cardiac autonomic modulation at rest. Additionally, the study aims to investigate the influence of family history and aerobic exercise on glycemia and cardiac autonomic modulation after a carbohydrate overload in young adults. Thirty-four volunteers (24.85 ± 5.33 years) were divided into: control group (n=16) (offspring of parents without T2DM (FHD-)), and condition group (n=18) FHD+. On the first visit, participants answered a physical activity level questionnaire and anthropometric measurements were collected. Subsequently, at the end of the rest period, glycemia and HRV were recorded. Then, a 30-minute rest or exercise period (balanced order) was applied and glycemia and HRV were recorded at the end of 30 minutes post-recovery (0 minutes). Afterwards, participants drank a dextrose solution. At 30 and 60 minutes after ingestion of the solution, glycemia and HRV were measured. The second visit addressed the condition that had not yet been performed. For statistical analysis, the Kolmogorov-Smirnov test was used to check data normality. An unpaired T-test and MannWhitney U test were performed to evaluate the influence of family history of T2DM on glycemia and resting MAC. To evaluate whether FHD+ and aerobic exercise influenced glycemia and dextrose overload, the peak delta and glycemic values at the evaluated times were used with Two-Way ANOVA. To evaluate HRV, the Mann-Whitney U test was used. The significance level adopted was p < 0.05. In the study results, there were no anthropometric differences between FHD+ and FHD-, physical activity level, and resting hemodynamic variables. However, FHD+ exhibited higher casual glycemia (118.33 ± 13.06 mg/dL) than the FHD- group (106.88 ± 11.23 mg/dL; p= 0.01; ES: 0.94). Glycemia after carbohydrate overload was not different between the FHD+ and FHD- groups (p= 0.89; ηp²=0.00), although it showed higher glycemic value at 30 min (143 mg/dL; p= 0.01; ηp²= 0.63). No interaction between group and time (p=0.97; ηp²=0.00). Additionally, the exercise condition did not influence glycemic control after dextrose overload between groups (p=0.80; ηp²= 0.00), however, it showed higher glycemia at 30 min regardless of the condition (141 mg/dL; p= 0.01; ηp²= 0.67). No interaction between condition and time (p=0.72; ηp²= 0.08). There was no difference between groups in HRV indices in both conditions. In conclusion, having a family history of type 2 diabetes in the absence of metabolic disorders impairs casual glycemia, but not HRV at rest, nor glycemia and HRV after carbohydrate overload in young adults. Additionally, 30 minutes of moderate exercise did not reduce glycemia after carbohydrate overload consumption.